2019
DOI: 10.1080/21691401.2019.1575842
|View full text |Cite
|
Sign up to set email alerts
|

A potential dermal substitute using decellularized dermis extracellular matrix derived bio-ink

Abstract: Upon bioprinting, cells are mixed with a biomaterial to fabricate a living tissue, thus emphasizing the importance of biomaterials. The biomaterial used in this study was a bio-ink prepared using skin decellularized extracellular matrix (dECM). Skin dECM was extracted by treating the dermis with chemicals and enzymes; the basic structural and functional proteins of the ECM, including collagen, glycosaminoglycans (GAGs), bioreactive materials and growth factors, were preserved, whereas the resident cells that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…Won and colleagues conducted another innovative study on decellularized ECM derived from a pig dermis; the authors obtained a printable bio-ink that was mixed with human dermal fibroblasts (HDFs) to produce a construct loaded with human cells. The residual ECM containing collagen and GAG, as well as bioactive molecules and growth factors, provided cells with an environment identical to that in the tissue, helping with the viability and proliferation of HDF in the construct [ 122 ].…”
Section: Scaffolds For Skin Tissue Engineering and Cutting-edge Tementioning
confidence: 99%
“…Won and colleagues conducted another innovative study on decellularized ECM derived from a pig dermis; the authors obtained a printable bio-ink that was mixed with human dermal fibroblasts (HDFs) to produce a construct loaded with human cells. The residual ECM containing collagen and GAG, as well as bioactive molecules and growth factors, provided cells with an environment identical to that in the tissue, helping with the viability and proliferation of HDF in the construct [ 122 ].…”
Section: Scaffolds For Skin Tissue Engineering and Cutting-edge Tementioning
confidence: 99%
“…A bio-ink prepared using skin decellularized ECM has been recently described [104]. The bio-ink was obtained by combining decellularized ECM (containing collagen, glycosaminoglycans and growth factors and free from immune-reactive cells) with human dermal fibroblasts.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Importantly, it was observed that co-culture systems have advantages over monocultures since fibroblasts have the ability to promote keratinocyte growth and differentiation by either GF release or direct cell-cell contact, whereas GFs secreted by keratinocytes stimulate fibroblast proliferation ( Figure 6) [2,49,50]. of skin cells purchased from the cell culture bank [71,72]. The main disadvantage of the use of isolated primary cells is their low proliferation potential, making it difficult to obtain a sufficient number of cells for cellular skin graft production [49].…”
Section: Cells Used For Cellular Skin Graft Productionmentioning
confidence: 99%
“…Nevertheless, it is known that cell lines may reveal a completely different gene expression compared to primary cells [65,66], and thus primary cultures should be preferentially used for both skin graft production and biocompatibility testing of new biomaterial-based skin substitutes. Indeed, most cellular artificial skins were developed using either isolated primary fibroblasts and/or keratinocytes [67][68][69][70] or primary culture of skin cells purchased from the cell culture bank [71,72]. The main disadvantage of the use of isolated primary cells is their low proliferation potential, making it difficult to obtain a sufficient number of cells for cellular skin graft production [49].…”
Section: Biomaterials Used For Skin Graft Productionmentioning
confidence: 99%
See 1 more Smart Citation